CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Kenneth S. Adeyemi; Lateef Olabisi Adedeji (Malete Journal of Accounting and Finance)
The role of capital structure decision is critical to the performance of any bank. For any bank to efficiently perform its function of financial intermediation, it must be financially structured. Against this backdrop, the study investigated the impact of capital structure on the financial performance of listed Deposit Money Banks (DMBs) in Nigeria spanning from 2006 to 2019. The study adopted panel data obtained from the annual reports and financial statements of the sampled listed DMBs on the Nigerian Stock Exchange. Descriptive and inferential statistics were used to examine the association between the dependent variable of financial performance proxied by the return on assets and independent variables represented by equity capital and leverage ratios while asset tangibility and liquidity were used as control variables. The results of both system dynamic panel Generalized Methods of Moment (GMM) estimator and Toda and Yamamoto (1995) granger non-causality model showed that equity capital significantly and positively affects return on assets (ROA) while leverage ratio significantly but negatively impacts on return on assets (ROA). There is also, a reverse causality relationship running from return on assets (ROA) to capital structure. Based on this, it is suggested that managements of DMBs should pursue financing policies that reduce reliance on debt finance and increases the use of retained profit as internal equity sources, in order to achieve the optimal level of capital structure for better and sustainable performance.